The role of human papillomavirus deoxyribonucleic acid for distinguishing between cervical adenocarcinoma and endometrial adenocarcinoma - Budi Harjanto; Suhatno Suhatno (Majalah Obstetri dan Ginekologi, 2021)
HIGHLIGHTS1. Determining primary tumor between uterine cervical adenocarcinoma and endometrial carcinoma is often complicated due to the lack of specimen or overlapped histological and morphological spectrum.2. The distinction between endometrial and endocervical adenocarcinoma preoperatively is important because the treatment is different.3. The samples from each group are tested for HPV DNA using PCR method.4. High risk HPV infected patients have a higher probability to become uterine cervical adenocarcinoma.5. HPV DNA test has a role for distinguishing between uterine cervical adenocarcinoma and endometrial carcinoma. ABSTRACTObjectives: To analyze the role of HPV DNA for distinguishing between uterine cervical adenocarcinoma and endometrial adenocarcinoma.Materials and Methods: This was a case control study using paraffin block samples from uterine cervix adenocarcinoma and endometrial adenocarcinoma operation at Dr. Soetomo General Academic Hospital, Surabaya, Indonesia. Each group was tested for HPV DNA using PCR method. Sample size was 18 in each group.Results: A total of 36 samples fulfilled the inclusion criteria in this study. Each group comprised 18 samples. There were 83.3% of uterine cervical adenocarcinoma and 11.1% of endometrial adenocarcinoma that revealed high risk HPV. Chi-Square test result found significant correlation between high risk HPV and uterine cervical adenocarcinoma (p<0.05) with Odds Ratio (OR) 40.00 (CI 95%).Conclusion: There was a significant correlation between high risk HPV and uterine cervix adenocarcinoma. High-risk HPV infected patients had a risk to suffer from uterine cervical adenocarcinoma compared to those with endometrial adenocarcinoma. HPV DNA test had a role for distinguishing between uterine cervical adenocarcinoma and endometrial adenocarcinoma.